In-Session Stuck Points and Pitfalls of Community Clinicians Learning CBT: Qualitative Investigation. Issue 2 (May 2017) - Waltman, Scott; Hall, Brittany C.; McFarr, Lynn M.; Beck, Aaron T.; Creed, Torrey A.
Abstract: Given the preponderance of evidence supporting the efficacy of cognitive behavior therapy (CBT), there has been an increased emphasis on dissemination to community mental health systems (CMH). Trainers from two large-scale dissemination initiatives ( n  = 27) were surveyed regarding the common pitfalls and difficulties encountered by CMH clinicians learning CBT. Common pitfalls were organized according to the items of the Cognitive Therapy Rating Scale (CTRS; Young & Beck, 1980) and reviewed. Guided discovery was reported to be the most challenging CBT competency to learn. Qualitative methods were used to construct a grounded theory; trainer responses indicated they viewed the practice of CBT as not only a set of discrete skills, but also a way of thinking. Efforts may be needed to provide support, assistance, and resources to these CMH clinicians as they continue to build CBT competency. Highlights: We examine the process of learning CBT. We review common pitfalls to learning CBT. Guided Discovery may be the most difficult to learn.